New fossil mesoserphid wasps (Insecta, Hymenoptera, Proctotrupoidea) from the Jehol Biota, China - Shi, Xiaoqing; Zhao, Yunyun; Shih, Chungkun; Ren, Dong (Zootaxa, 2013)
A new genus with two new species, Codoserphus calophlebius gen. et sp. nov. and Codoserphus euneurus gen. et sp. nov., assigned to the subfamily Mesoserphinae of Mesoserphidae, are described from the Jehol Biota, Early Cretaceous Yixian Formation of Huangbanjigou Village in Liaoning, China. Codoserphus gen. nov. is characterized by its fore wing with all major veins present, not reduced, and 1cu-a distal to 1-M in fore wing. An updated key is given for the genera of Mesoserphidae from around the world.